The Effectiveness of the TOSS Program in Waste Management in Klungkung Regency: Integrating the Principles of the Neo-Weberian State in Environmental Policy - Suariyanti, Ni Wayan Nina; Wardiyanto, Bintoro; Setijaningrum, Erna (Jurnal Pemerintahan dan Politik, 2025)
Waste management is a complex issue that requires innovative and sustainable approaches. Klungkung Regency faces challenges in waste management, including increasing waste volume, limited infrastructure, and low community participation. The Klungkung Regency Government has implemented the Local Waste Processing Site (TOSS) Program as an innovative strategy for managing waste into alternative energy sources. This study analyzes the effectiveness of waste management policies and the implementation of the Neo-Weberian State (NWS) principles in environmental governance in Klungkung. The research method used is a literature study with a qualitative descriptive approach. The results of the study indicate that although the TOSS Program has had a positive impact in reducing waste generation and creating economic opportunities, various obstacles are still faced, especially in terms of community participation and supporting infrastructure. Therefore, a more effective, innovative, and sustainable strategy is needed to improve the success of waste management in the Klungkung Regency.